ANALISIS PAPAN KOMPOSIT DARI LIMBAH PLASTIK POLYPROPHYLENE (PP) DAN SEKAM PADI - Nurjannah, Nurjannah; Hernawati, Hernawati; Rahmaniah, Rahmaniah (JFT : Jurnal Fisika dan Terapannya, 2015)
This study aims to determine the quality of the composite board from a variety of compositions. The sample composition consisted of 50% polypropylene plastic: 50% rice husk, 60% polypropylene plastic: 40% rice husk, 70% polypropylene plastic: 30% rice husk and 80% polypropylene plastic: 20% rice husk. The method used in this research is physical test and mechanical test. As for the results of the physical properties test, the density test of all compositions meets the standards starting from the low, medium and high density composite board category. To test the moisture content of all compositions meet the standards. Meanwhile, in the water absorption test, there was no composition that met the standards. For the thickness change test, all compositions met the standards except for the composition of 50% polypropylene plastic: 50% rice husk. The test results for the mechanical properties of all compositions do not yet meet Indonesian national standards.